The Effect Of Implementing Whole Language Approach To Improve Third-Grade Elementary Students’ Early Reading Skills - Annisa Putri Permatasari1; Devita Ayu Lazuarni; Nathasya Ayu Wulandari; Yurniwati; Yofita Sari (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2023)
Early reading is the initial level in the process of learning to read. Early reading skills play an important role in developing advanced reading skills. The study aims to determine the effect of applying the whole language approach by using picture storybooks to improve elementary students’ early reading skills in grade III. The research was conducted in Cipinang Besar Selatan. The research applied an experimental study with Pretest-Posttest Control Group Design. Data were collected using 20 multiple-choice question-item tests. Data were analyzed through normality, homogeneity, and paired sample t-test tests. The hypothesis test results indicate t = 3.162 with pvalue of 0.006. The conclusion of the research is that there is a significant positive effect of the whole language approach on third-grade elementary students’ early reading skills. Learning using the whole language approach can be used as an alternative to improving third-grade elementary students’ early reading skills. Picture storybooks make students more interested in reading and picture illustrations help students more easily understand the reading content in the learning material.